(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the formation of mass media (mass media), stages of historical development and their role in the social and political life of society. The author draws attention to the role of mass media in political socialization, formation of public opinion and participation in democratic processes, in addition to information transmission. Also, the transformation of the mass media system under the influence of digital technologies and its role in the new communication environment are highlighted.